Pemberdayaan Ekonomi Masyarakat Desa Kampili melalui Inovasi Minuman Cincau Kekinian - Ansar, Ansar; Arfah, Aziza Noor Sheha; Mahi, Faizah; Hasan, Hasna (Pakis Journal Institute, 2025)
Empowerment of Kampili Village Community Economy Through Innovative Cincau Drinks The utilization of cincau as a fiber-rich food ingredient in Kampili Village is still limited, even though the current beverage trend opens significant economic opportunities. This community service aims to empower the economy of the Kampili Village community through the program